Modeling of fire in school building using computational fluid dynamics and development of evacuation time equation in Putrajaya, Malaysia - Nasruddin, Hairul Nazmin (2019)
School’s building fire had claimed many injuries, death and damage properties. While experimental on large scale fire to analyse the fire behaviour is impossible, the unknown fire pattern in a building and the students’ evacuation performance made the situation worst. In the first objective, the fire prediction and simulation in the school’s building was done by using Computational Fluid Dynamic (CFD) approach through Fire Dynamic Simulator (FDS) program. The model inputs were generated by using the interface program called Pyrosim. The subsequent objective is to develop a validated knowledge, attitude and practice (KAP) questionnaire and to develop the numerical formula for individual evacuation time estimation based on KAP, human characteristics, and travel distances. In CFD, the school model was constructed following the actual building specifications as in building floor plans and direct measurement. The four fire effluents (oxygen, carbon monoxide, temperature, and visibility) were studied for 250kW/m² and 2500kW/m² fire started in the classroom and laboratory. Relevant literatures were used to develop the KAP questionnaire and the validation was done through Content Validity test involving 11 experts. The totals of 290 secondary students were involved in the study. Every student’s evacuation time was obtained through direct calculation during the fire drill. The KAP questionnaires have been distributed among the students to obtain the personal details and to test their KAP level. The relationship between the calculated evacuation time and the respected three components are done by using Multiple Linear Regression (MLR) to generate estimation formula. The first objective was achieved through prediction of fire patterns in the school building in respect to four fire effluents. In the subsequent objective, a validated KAP questionnaire was constructed consists of 9 questions for knowledge assessment and 13 and seven questions for attitude and practice respectively. The development of formula estimating the individual evacuation time indicates the achievement of the last objective. The developed formula was integrated with the mobility factors to make it practicable in various circumstances. The study findings’ has revealed the potential fire risks and the factors contributing to students’ performance at school when dealing with fire. The predicted consequences of fire disaster are varied depending on the fire situation and students’ criteria. It is recommended that the related stakeholders to consider the building and students’ factors in decision making especially in the allocation of student’s classrooms. In conclusion, the study has developed a model to predict the fire behaviour at school. Subsequently, a numerical model was established to predict the individual evacuation time.